Mobile application features effects on the application's engagement and intention for continuing use in tourism - Ilkan, Sensev Payan; Ozturen, Ali; Avci, Turgay; Irani, Foad (Routledge Journals, Taylor & Francis Ltd, 2023)
The study intends to detect the impacting factors of mApp (mobile application) engagement and the intention for continuing use. The study investigates the conceptual model using the Diffusion of Innovation Theory (DOI) and Uses and Gratifications Theory (UGT). An online survey questionnaire was administered to European consumers. Outcomes show that DOI elements and UGT element playfulness significantly affect user satisfaction and perceived value. Furthermore, user satisfaction positively impacts mApp engagement and intention to continue using it. Exploring consumers' mApp perceptions can have practical implications for tourism organizations and mApp developers seeking better comprehension of respective customer groups' needs.
Keywords: Mobile tourism application; mobile technology; diffusion of innovation theory (DOI); uses and gratifications theory (UGT); mapp engagement; intention to continuing use